Samanvaya ke sādhaka : Śrī Kākāsāheba Kālelakara abhinandana grantha - Kalelkar, Dattatraya Balakrishna, 1885-; Jain, Yashpal, 1912-; Nāṇāvaṭī, Sarojinī; Vyāsa, Hasamukha, 1927- (Śrī Kākāsāheba Kālelakara Abhinandana Samiti : Mukhya vikretā, Sastā Sāhitya Maṇḍala, 1979)
Festschrift honoring Dattatraya Balkrishna Kalelkar, b.1885, Indian litterateur and social and political activist; includes selections from his writings in translation.